Karakteristik Minyak Bumi di Blok Bula dan Blok Oseil, Pulau Seram, Maluku - Wahyudiono, Joko; Adlan, Ryandi; Permanadewi, Sam; Gibran, Akhmad Khahlil (Jurnal Geologi dan Sumberdaya Mineral, 2018)
Oil that produced in a petroleum system must have specific characteristics depend on the source rocks. These characteristics are able to be understood by analyses of organic geochemistry. Gas Chromatography - Mass Spectrometry (GC-MS) is a very accurate tool for determining the characteristics of oil and gas. This research shows the evidence that oil samples taken from Bula Block and Oseil Block, Seram Island have the same source.Keywords: petroleum system, organic geochemistry, Bula, Oseil, Seram Island